Carbon nitride loaded metal diatom photocatalytic material as well as preparation method and application thereof

By loading the same metal atoms on the surface of carbon nitride to form a metal diatom structure, the problems of complex preparation process and low photocatalytic efficiency in the prior art are solved, and efficient photocatalytic reactions are achieved, especially during the carbon dioxide reduction process.

CN119588397APending Publication Date: 2025-03-11HEILONGJIANG UNIV

Patent Information

Application Number
CN202411779056.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The preparation process of existing metal diatom photocatalysts is complicated and the photocatalytic efficiency is not high.

Method used

By loading the same metal atoms on the surface of carbon nitride, the structure of metal diatoms is formed, and the synthesis is carried out using simple process steps, including hydrothermal reaction, reflux treatment and sonication.

Benefits of technology

The activity and stability of the photocatalyst is improved and the efficiency of the photocatalytic reaction is significantly improved. Especially in the reaction of carbon dioxide reduction to carbon monoxide and methane, the catalytic rate is increased by more than three times and good cycle stability is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588397A_ABST
    Figure CN119588397A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon nitride loaded metal diatom photocatalytic material as well as a preparation method and application thereof. The invention belongs to the field of photocatalytic materials. The invention aims to solve the technical problems of complex preparation process and low photocatalytic efficiency of the existing metal diatom photocatalyst. The method comprises the following steps: dissolving a nitrogen source and a phosphorus source in deionized water, and carrying out hydrothermal reaction to obtain a precursor; dissolving the precursor in a mixed solvent of alcohol, and then refluxing at constant temperature for a certain time to obtain a pre-product; and adding a metal compound solution capable of forming a conjugated system into the pre-product, carrying out ultrasonic treatment, heating in a constant-temperature water bath kettle, and calcining to obtain the carbon nitride loaded metal diatom photocatalytic material. The obtained photocatalytic material has the advantages of high visible light utilization rate, low photo-induced electron-hole recombination rate and high electron transfer rate. The method is used in the fields of photocatalytic hydrogen production, carbon dioxide reduction and organic matter oxidation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photocatalytic materials, and in particular relates to a carbon nitride-loaded metal diatomic photocatalytic material and a preparation method and application thereof. Background Art

[0002] The acceleration of urbanization and industrialization, accompanied by population growth and rising consumption levels, has led to an increasing amount of carbon dioxide emissions worldwide. As one of the greenhouse gases, the excessive accumulation of carbon dioxide has caused a series of environmental problems, such as global warming, extreme climate change, melting of polar glaciers, rising sea levels, and ocean acidification. These problems have not only had a devastating impact on the ecosystem, but also threatened human survival and development. In order to meet this challenge, the scientific and engineering communities are actively seeking effective solutions for carbon dioxide emission reduction and harmless treatment, while also studying related technologies for photocatalytic hydrogen production and organic matter oxidation. In recent years, the application of photocatalytic technology has gradually received attention, especially in the process of capturing and converting carbon dioxide into high-value-added chemicals and energy. Photocatalytic reactions use renewable solar energy, which is not only sustainable, but also can achieve efficient conversion and storage of energy. In addition, hydrogen generated by photocatalytic reactions as a clean energy can significantly reduce dependence on fossil fuels, thereby alleviating the dual pressures of resource depletion and environmental pollution.

[0003] Among various photocatalytic materials, graphite carbon nitride (g-C3N4) as a semiconductor has the best band gap (2.7eV), can effectively utilize visible light (λ<470nm), and has excellent thermal and chemical stability, environmental protection and cost-effectiveness, making it a very promising photocatalytic material. However, due to the defects of C3N4 such as high recombination rate of photogenerated electron-hole pairs, slow charge transfer and insufficient absorption and utilization of visible light, its further application is severely limited. In the process of solving these problems, researchers are actively exploring ways to improve the catalytic performance of g-C3N4. One of the effective strategies is to introduce diatomic catalysts. However, the existing C3N4-loaded diatomic catalysts generally have the problems of complex preparation process and low photocatalytic efficiency. Summary of the invention

[0004] The purpose of the present invention is to solve the technical problems that the preparation process of existing metal diatomic photocatalysts is complicated and the photocatalytic efficiency is low, and to provide a carbon nitride-loaded metal diatomic photocatalytic material and its preparation method and application.

[0005] One of the purposes of the present invention is to provide a method for preparing a carbon nitride-supported metal diatomic photocatalytic material, the method being carried out according to the following steps:

[0006] S1: dissolving a nitrogen source and a phosphorus source in deionized water, and then maintaining the mixture in a constant temperature water bath to obtain a mixed solution, and then transferring the mixture into a high pressure hydrothermal reactor for hydrothermal reaction. After the reaction, washing and drying the precipitate to obtain a precursor;

[0007] S2: dissolving the precursor in a mixed solvent of alcohol, then refluxing at a constant temperature for a certain period of time, and drying the precipitate after reflux to obtain a pre-product;

[0008] S3: Add a metal compound solution that can form a conjugated system to the pre-product, heat it in a constant temperature water bath after ultrasonic treatment, and stir while heating until it becomes a viscous precipitate, then stop drying, grinding, and calcining to obtain a carbon nitride-loaded metal diatomic photocatalytic material.

[0009] It is further defined that the nitrogen source in S1 is melamine, dicyandiamide or cyanuric acid, and the phosphorus source is phosphoric acid or solid phosphorous acid.

[0010] It is further defined that the ratio of nitrogen source, phosphorus source and deionized water in S1 is 1 g:1.2 g:(60-100) mL.

[0011] It is further defined that the temperature of the constant temperature water bath in S1 is 60-90°C and maintained for 0.5-2h.

[0012] It is further defined that the hydrothermal reaction temperature in S1 is 150-200°C and the reaction time is 8-12h.

[0013] It is further defined that the drying temperature in S1 is 45-65° C. and the drying time is 8-12 h.

[0014] It is further defined that the alcohol mixed solvent in S2 is selected from two or more alcohol organic solvents.

[0015] In a further aspect, the alcohol organic solvent includes methanol, ethanol, propanol, ethylene glycol and glycerol.

[0016] It is further defined that the ratio of the mixed solvent of the precursor and the alcohol in S2 is (0.4-0.8) g: (10-30) mL.

[0017] It is further defined that the reflux temperature in S2 is 60-90° C. and the reflux time is 2-6 h.

[0018] It is further defined that the drying temperature in S2 is 45-65° C. and the drying time is 6-10 h.

[0019] It is further defined that the metal compound in S3 is selected from sodium copper chlorophyllin, sodium iron chlorophyllin, copper phthalocyanine or iron phthalocyanine.

[0020] It is further defined that the concentration of the metal compound solution in S3 is 0.2-0.8 g / L, and the ratio of the metal compound solution to the pre-product is 10 mL: (0.6-1.2) g.

[0021] It is further defined that the water bath temperature in S3 is 60-90°C, the time is 2-4h, and the stirring speed is 500-1000rpm.

[0022] It is further defined that the drying temperature in S3 is 40-60° C. and the drying time is 2-5 h.

[0023] It is further defined that the heating rate of calcination in S3 is 1-5°C / min, the temperature is raised to 300-600°C, and the temperature is kept for 1-4h, and the calcination is carried out under a protective atmosphere.

[0024] It is further defined that the protective atmosphere is nitrogen or argon, and the gas flow rate is 40-80 mL / min.

[0025] The second object of the present invention is to provide a carbon nitride-loaded metal diatomic photocatalytic material obtained by the above method, wherein the diatomic atoms are of the same metal.

[0026] The third object of the present invention is to provide an application of the carbon nitride-loaded metal diatomic photocatalytic material obtained by the above method in photocatalytic hydrogen production, carbon dioxide reduction and organic matter oxidation reactions.

[0027] Compared with the prior art, the present invention has the following significant effects:

[0028] The present invention forms a metal diatomic structure by loading metal atoms on the surface of carbon nitride. The activity and stability of the photocatalyst are improved, and the related catalytic reactions are promoted. When light is irradiated to the surface of the carbon nitride loaded metal diatomic photocatalyst, the metal atoms can accept light-excited electrons from the carbon nitride surface like conduction electrons, forming active sites in the metal-diatom structure. These active sites can adsorb reactants and promote the progress of chemical reactions under the action of light, thereby achieving an enhanced effect of the photocatalytic reaction. At the same time, metal atoms can also help reduce the recombination of electron-hole pairs, and improve the stability and recycling rate of the photocatalyst. The specific advantages are as follows:

[0029] (1) The present invention uses a simple process to load the same type of diatoms on C3N4 in one step, which can produce a synergistic effect at the catalytic site, thereby significantly improving the efficiency of the photocatalytic reaction. The high atomic utilization rate of this type of catalyst helps to reduce the photogenerated electron-hole recombination rate, improve the electron transfer rate, and further optimize the photocatalytic performance;

[0030] (2) The unique structure and physicochemical properties of carbon nitride used in the present invention and the excellent electron conduction efficiency of metal atoms open up new possibilities for developing catalysts with better photocatalytic activity, stability and selectivity;

[0031] (3) The present invention realizes the controllable synthesis of carbon nitride-supported bimetallic atom photocatalyst by regulating variables such as material feed ratio and heat treatment heating rate;

[0032] (4) The present invention can synthesize a porous thin-layer photocatalyst by simply refluxing and heat treating. Compared with the traditional synthesis method, the synthesis method is relatively simple and environmentally friendly, and this method can save a lot of experimental materials;

[0033] (5) The present invention adjusts the ratio of the metal compound solution and the precursor used to form a large conjugated system, so that the prepared carbon nitride-supported metal diatomic photocatalytic material can photocatalytically reduce carbon dioxide to carbon monoxide at a rate of 64.5 μmol·g under visible light irradiation. -1 ·h -1 The good performance and excellent cycle stability of methane are 0.8 μmol·g -1 ·h -1 Compared with the control test, the photocatalytic reduction rate of carbon dioxide to carbon monoxide in the material without the conjugated metal compound solution under visible light irradiation was 19.3 μmol·g -1 ·h -1 , the methane rate is 1.2 μmol·g -1 ·h -1 It can be seen that the prepared carbon nitride-loaded metal diatomic photocatalytic material plays an important role in improving the rate of carbon dioxide reduction to carbon monoxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a SEM image of the precursor prepared in step (1) of Example 1;

[0035] Figure 2 This is a SEM image of the carbon nitride-supported metal diatomic photocatalytic material prepared in Example 1;

[0036] Figure 3 The ultraviolet-visible light absorption spectra of the carbon nitride prepared in Comparative Example 1 and the carbon nitride-supported metal diatomic photocatalytic material prepared in Example 1;

[0037] Figure 4 Electrochemical impedance spectroscopy of carbon nitride prepared in Comparative Example 1 and carbon nitride-supported metal diatomic photocatalytic material prepared in Example 2;

[0038] Figure 5The graph is a rate diagram of photocatalytic reduction of carbon dioxide to carbon monoxide and methane under simulated sunlight for the photocatalytic materials of Comparative Example 1 and Example 1. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0040] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0041] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0042] The "one embodiment" or "embodiment" of the present invention refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. The "in one embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0043] The endpoints and any values ​​of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.

[0044] Example 1: The preparation method of the carbon nitride-supported metal diatomic photocatalytic material of this example is carried out according to the following steps:

[0045] (1) 1.0 g of melamine and 1.2 g of solid phosphorous acid were added to 75 mL of deionized water, placed on a stirrer and stirred for 0.5 h at a speed of 500 r / min until a uniform solution was formed, and then the solution was placed in a constant temperature water bath and the temperature was set to 80° C. and maintained for 1 h to obtain a mixed solution; the mixed solution was transferred to a polytetrafluoroethylene high-pressure hydrothermal autoclave, placed in a vacuum oven at a temperature of 180° C. and kept warm for 10 h, then naturally cooled to room temperature, and the precipitate was collected and washed with deionized water and anhydrous ethanol for 3 times, respectively, and the centrifugal speed was 4000 r / min, and the centrifugal time each time was 3 min. Finally, the precipitate was placed in a vacuum oven and dried for 10 h at a drying temperature of 60° C. to obtain a precursor; Figure 1 This is the SEM image of the precursor prepared in step (1) of Example 1. It can be seen that the precursor presents a hexagonal prism structure.

[0046] (2) 0.6 g of the precursor was added to a mixed solvent of 15 mL of anhydrous ethanol and 5 mL of ethylene glycol, and the mixture was stirred to obtain a mixed solution. The mixed solution was refluxed at a constant temperature of 80° C. for 3 h. The mixed solution obtained after reflux was centrifuged and washed with deionized water and anhydrous ethanol for 3 times, respectively, at a centrifugal speed of 8000 r / min, and the centrifugal time of each time was 5 min to obtain a precipitate; the precipitate was placed in a vacuum oven for drying at a drying temperature of 60° C. for 8 h to obtain a pre-product;

[0047] (3) Dissolve 50 mg of sodium copper chlorophyllin powder in deionized water, stir for 3 h in dark, and then adjust the volume of the mixed solution to 100 mL to obtain a metal compound solution; add 10 mL of the metal compound solution to 0.6 g of the pre-product and perform ultrasonic treatment for 10 min. Then put the ultrasonically treated solution into a constant temperature water bath and set the temperature to 80 ° C while rapidly stirring it for 2.5 h at a stirring speed of 800 r / min. After the mixed solution becomes a viscous precipitate, put it into a vacuum oven, dry it at a temperature of 50 ° C, dry it for 3 h, grind it and put it into a porcelain boat, put the porcelain boat into a tube furnace, heat the tube furnace in a nitrogen (50 mL / min) atmosphere, heat it at a rate of 2 ° C / min, heat it to 520 ° C and keep it warm for 2.5 h, and naturally cool it to room temperature to obtain a carbon nitride-supported metal diatomic photocatalytic material (Cu-Cu / C3N4). Figure 2 This is a SEM image of the carbon nitride-supported metal diatomic photocatalytic material prepared in Example 1; Figure 2 It can be seen that the surface of the carrier has a lamellar structure, and the addition of metallic copper can make the surface of the carrier looser and the delamination more obvious.

[0048] Example 2: The preparation method of the carbon nitride-supported metal diatomic photocatalytic material of this example is carried out according to the following steps:

[0049] (1) 1.0 g of melamine and 1.2 g of solid phosphorous acid were added to 75 mL of deionized water, placed on a stirrer and stirred for 0.5 h at a speed of 500 r / min until a uniform solution was formed, and then the solution was placed in a constant temperature water bath and the temperature was set to 80° C. and maintained for 1 h to obtain a mixed solution; the mixed solution was transferred to a polytetrafluoroethylene high-pressure hydrothermal autoclave, placed in a vacuum oven at a temperature of 180° C. and kept warm for 10 h, then naturally cooled to room temperature, and the precipitate was collected and washed with deionized water and anhydrous ethanol for 3 times, respectively, and the centrifugal speed was 4000 r / min, and the centrifugal time each time was 3 min. Finally, the precipitate was placed in a vacuum oven and dried for 10 h at a drying temperature of 60° C. to obtain a precursor;

[0050] (2) 0.6 g of the precursor was added to a mixed solvent of 15 mL of anhydrous ethanol and 5 mL of ethylene glycol, and the mixture was stirred to obtain a mixed solution. The mixed solution was refluxed at a constant temperature of 80° C. for 3 h. The mixed solution obtained after reflux was centrifuged and washed with deionized water and anhydrous ethanol for 3 times, respectively, at a centrifugal speed of 8000 r / min, and the centrifugal time of each time was 5 min to obtain a precipitate; the precipitate was placed in a vacuum oven for drying at a drying temperature of 60° C. for 8 h to obtain a pre-product;

[0051] (3) Dissolve 50 mg of sodium iron chlorophyll powder in deionized water, stir for 3 h in dark, and then adjust the volume of the mixed solution to 100 mL to obtain a metal compound solution; add 10 mL of the metal compound solution to 0.6 g of the pre-product and perform ultrasonic treatment for 10 min. Then put the ultrasonically treated solution into a constant temperature water bath and set the temperature to 80 ° C while rapidly stirring it for 2.5 h at a stirring speed of 800 r / min. After the mixed solution becomes a viscous precipitate, put it into a vacuum oven, dry it at a temperature of 50 ° C, dry it for 3 h, grind it, put it into a porcelain boat, put the porcelain boat into a tube furnace, heat the tube furnace in a nitrogen (50 mL / min) atmosphere, heat it at a rate of 2 ° C / min, heat it to 520 ° C and keep it warm for 2.5 h, and naturally cool it to room temperature to obtain a carbon nitride-supported metal diatomic photocatalytic material (Fe-Fe / C3N4).

[0052] Comparative Example 1: The preparation method of the photocatalytic material of this comparative example is carried out according to the following steps:

[0053] (1) 1.0 g of melamine and 1.2 g of solid phosphorous acid were added to 75 mL of deionized water, placed on a stirrer and stirred for 0.5 h at a speed of 500 r / min until a uniform solution was formed, and then the solution was placed in a constant temperature water bath and the temperature was set to 80° C. and maintained for 1 h to obtain a mixed solution; the mixed solution was transferred to a polytetrafluoroethylene high-pressure hydrothermal autoclave, placed in a vacuum oven at a temperature of 180° C. and kept warm for 10 h, then naturally cooled to room temperature, and the precipitate was collected and washed with deionized water and anhydrous ethanol for 3 times, respectively, and the centrifugal speed was 4000 r / min, and the centrifugal time each time was 3 min. Finally, the precipitate was placed in a vacuum oven and dried for 10 h at a drying temperature of 60° C. to obtain a precursor;

[0054] (2) 0.6 g of the precursor was added to a mixed solvent of 15 mL of anhydrous ethanol and 5 mL of ethylene glycol, and the mixture was stirred to obtain a mixed solution. The mixed solution was refluxed at a constant temperature of 80° C. for 3 h. The mixed solution obtained after reflux was centrifuged and washed with deionized water and anhydrous ethanol for 3 times, respectively, at a centrifugal speed of 8000 r / min, and the centrifugal time of each time was 5 min to obtain a precipitate; the precipitate was placed in a vacuum oven for drying at a drying temperature of 60° C. for 8 h to obtain a pre-product;

[0055] (3) Grind the pre-product and put it into a porcelain boat, which is then placed into a tubular furnace. The tubular furnace is heated in a nitrogen atmosphere (50 mL / min) at a rate of 2°C / min to 520°C and kept at this temperature for 2.5 h. The photocatalytic material (C3N4) is obtained after naturally cooling to room temperature.

[0056] Figure 3 The ultraviolet-visible light absorption spectra of the carbon nitride of Comparative Example 1 and the carbon nitride-supported metal diatomic photocatalytic material prepared in Example 1; Figure 3 It can be seen that the addition of metal Cu atoms significantly broadens the visible light absorption range of the composite material.

[0057] Figure 4 The electrochemical impedance spectra of the carbon nitride supported metal diatomic photocatalytic material prepared in Comparative Example 1 and Example 2 are shown in FIG. Figure 4 It can be seen that in the EIS spectrum, the order of arc diameter is: C3N4>Fe-Fe / C3N4, indicating that Fe-Fe / C3N4 has the lowest charge transfer resistance and is more conducive to effective carrier migration.

[0058] Application Example 1: The photocatalytic CO2 reduction performance of the catalyst was evaluated using a Labsolar 6A online testing device. First, 10 mg of photocatalyst and 3 mL of H2O were added to the reaction vessel, a vacuum pump was used to remove the air in the instrument and the gases dissolved in the water as much as possible, and then CO2 (purity: 99.999%) was filled into the instrument until the pressure in the instrument was 80 kPa. The reactor was kept for 30 min to establish adsorption-desorption equilibrium. A 300 W xenon lamp was used as the light source. No co-catalyst or sacrificial agent was used during the photocatalytic reaction. The photocatalytic reactor was connected to an online gas chromatograph for gas collection and analysis. The gas products were analyzed using a gas chromatograph equipped with a flame ionization detector and a thermal conductivity detector.

[0059] The rates of photocatalytic reduction of carbon dioxide to carbon monoxide and methane under visible light irradiation of the carbon nitride-supported metal diatomic photocatalytic material prepared in Example 1 and the carbon nitride photocatalytic material prepared in Comparative Example 1 are shown in FIG. Figure 5 As shown in the figure, the rate of catalytic reduction of carbon dioxide to produce CO by the carbon nitride-supported metal diatomic photocatalytic material prepared in Example 1 is 64.5 μmol·g -1 ·h -1 , the rate of CH4 is 0.8 μmol·g -1 ·h -1 The carbon nitride photocatalytic material prepared in Comparative Example 1 showed a photocatalytic reduction rate of carbon dioxide to CO of only 19.3 μmol·g under visible light irradiation. -1 ·h -1 , the rate of CH4 is 1.2 μmol·g -1 ·h -1 Compared with a single porous few-layer C3N4 photocatalyst, the rate of photocatalytic reduction of carbon dioxide to carbon monoxide by the carbon nitride-supported metal diatomic photocatalytic material of the present invention can be increased by more than three times.

[0060] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a carbon nitride-supported metal diatomic photocatalytic material, characterized in that: The method: S1: dissolving a nitrogen source and a phosphorus source in deionized water, and then maintaining the mixture in a constant temperature water bath to obtain a mixed solution, and then transferring the mixture into a high pressure hydrothermal reactor for hydrothermal reaction. After the reaction, washing and drying the precipitate to obtain a precursor; S2: dissolving the precursor in a mixed solvent of alcohol, then refluxing at a constant temperature for a certain period of time, and drying the precipitate after reflux to obtain a pre-product; S3: Add a metal compound solution that can form a conjugated system to the pre-product, heat it in a constant temperature water bath after ultrasonic treatment, and stir while heating until it becomes a viscous precipitate, then stop drying, grinding, and calcining to obtain a carbon nitride-loaded metal diatomic photocatalytic material.

2. The method according to claim 1, characterized in that In S1, the nitrogen source is melamine, dicyandiamide or cyanuric acid, the phosphorus source is phosphoric acid or solid phosphorous acid, and the ratio of the nitrogen source, phosphorus source and deionized water is 1g:1.2g:(60-100)mL.

3. The method according to claim 1, characterized in that The constant temperature water bath in S1 is 60-90°C for 0.5-2h, and the hydrothermal reaction temperature is 150-200°C for 8-12h.

4. The method according to claim 1, characterized in that: The alcohol mixed solvent in S2 is selected from two or more alcohol organic solvents, and the ratio of the precursor to the alcohol mixed solvent is (0.4-0.8) g: (10-30) mL.

5. The method according to claim 4, characterized in that Alcohol organic solvents include methanol, ethanol, propanol, ethylene glycol and glycerol.

6. The method according to claim 1, characterized in that The reflux temperature in S2 is 60-90°C and the reflux time is 2-6h.

7. The method according to claim 1, characterized in that The metal compound in S3 is selected from sodium copper chlorophyllin, sodium iron chlorophyllin, copper phthalocyanine or iron phthalocyanine, the concentration of the metal compound solution is 0.2-0.8 g / L, and the ratio of the metal compound solution to the pre-product is 10 mL: (0.6-1.2) g.

8. The method according to claim 1, characterized in that The water bath temperature in S3 is 60-90°C, the time is 2-4h, the stirring speed is 500-1000rpm, the heating rate of calcination is 1-5°C / min, the temperature is raised to 300-600°C, and kept warm for 1-4h. The calcination is carried out under a protective atmosphere.

9. The carbon nitride-supported metal diatomic photocatalytic material obtained by the method according to any one of claims 1 to 8, characterized in that: The diatoms are of the same metal.

10. Use of the carbon nitride-supported metal diatomic photocatalytic material according to claim 9 in photocatalytic hydrogen production, carbon dioxide reduction and organic matter oxidation reactions.

Citation Information

Patent Citations

  • Preparation method of mono-atomic metal-carbon composite catalyst for electro-catalytic reactions

    CN106944057A

  • Preparation method of carbon nitride-based monatomic catalyst as well as product and application of carbon nitride-based monatomic catalyst

    CN113457713A

  • Carbon nitride-based site-specific double-monatomic catalyst as well as preparation and application of carbon nitride-based site-specific double-monatomic catalyst

    CN115007186A

Cited By

  • Ni-Co double-monatomic catalyst as well as preparation method and application thereof

    CN121496458A